The relationship of the University of the Philippines College of Law library's organizational culture to its staff job satisfaction - Garcia, Patricia Dianne S.; Cornago, Pia Charmaine F. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
According to Edgar Schein, organizational culture is a pattern of shared assumptions that are learned by a groupthat has worked well to be taught to new members as the standard way of doing things. Studies of Ritchie (2000) and Mehr et al (2012) concluded that organizational culture affect performance and productivity. While various researchers provided that job satisfaction is dependent on organizational variables. There are only few studies about organizational culture and job satisfaction that were conducted in the Philippines and in Philippine libraries in particular. This study was conducted among the staff of the UP College of Law Library in UP Diliman and determined the relationship between the library's organizational culture to its staff job satisfaction.
A quantitative method of data collection was carried out. The organizational culture was identified using the Organizational Culture Assessment Instrument, while the staff job satisfaction rate was measured using the Minnesota Satisfaction Questionnaire. Fifteen (15) out of sixteen (16) library staff of the institution responded to the survey questionnaire.
The data gathered from the survey questionnaires showed that the dominant type of organizational culture that UP College of Law Library is a Clan type of culture with an average score of 476.67, which identifies the culture of the library as friendly, open, and is held together by loyalty and tradition. The Hierarchy type of culture is the second dominant type of organizational culture with an average score of 410.27, which also identifies the environment as very formal and structured. The satisfaction score of the respondents is 3.99 out of 5, which identifies that the library staff are 'Satisfied' with their jobs. At a 95% confidence interval, the study revealed that the relationship between organizational culture and staff job satisfaction is not statistically significantly different from 0 but has a very weak negative inverse correlation at -.155 correlation coefficient and .427 p-value using Kendall's Tau; and -.217 correlation coefficient and .438 p-value using Spearman's Rho.
The study led to a conclusion that they have a friendly type of organizational culture in the library and such culture does not affect the satisfaction of the staff towards their jobs. It can be because of the presence of formal procedures that govern the staff. Analysis of the preferred organizational culture and its correlation to current staff job satisfaction were also considered in this research.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) College of Law Library; Library employees -- Job satisfaction -- Philippines -- Quezon City; Organizational behavior -- University of the Philippines -- College of Law Library; Corporate culture -- Philippines -- Quezon City